Analysis of Islamic Education Existence in the National Education System in the Aspect of Education Funding Policy in Indonesia - Shobirin Shobirin; Fauzi Fauzi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This article discusses the analysis of the existence of Islamic education in the national education system in the aspect of the education budget related to the study of Islamic education policies in Indonesian legislation. This study uses a qualitative approach with a qualitative descriptive type of research through a literature research study method. This encourages the need for the reconstruction of national education system policies in the budgetary aspect of educational institutions globally. This article analyzes that the existence of Islamic education in Indonesia in the national education system is a subsystem in national education, but it has not received the same attention as other education sectors. So this study criticizes the need for the reconstruction of national education system policy regulations on the aspects of the education budget in Indonesia and the solution to the existence of Islamic education in the national education system in the aspect of the education budget in Indonesia as an effort to reconstruct education policies in Indonesia offered by the author and input in the preparation. The education road map program in Indonesia by Commission X DPR RI on the direction of education development is the first, the concept of education equilibrium. The government issued a policy to equalize the education budget globally to end the dichotomy of education budget policies so far so that the existence of Islamic education is equal to the existence of other general education. Second, the separation between national education policies and political interests through the appointment of the minister of religion and the minister of the Ministry of Education and Culture-Research and Technology with professional figures is not based on entrusted elements from supporting parties/coalitions.